Sobre uma identidade envolvendo funções simétricas e partições de inteiros - Alegri, Mateus (2020)
In this work, we demonstrate a ’sum = product’ type identity of hypergeometric series related to the integer partitions and complete homogeneous symmetric functions, hn. For the proof of the result, we use the graphical tool called Ferrers Diagram. From this, with a simple change of variables, the main result is obtained, which is linked to a famous MacMahon identity.